CSR: friend or foe? Framing NGO Strategy through CSR in the Pursuit of Sustainable Funding - Singleton, Sarah (2006)
Through the application of frame analysis, corporate social responsibility (CSR) can currently be envisaged in relation to two extreme frames in analysing CSR as an interface for business-NGO collaborations: an altruistic frame (involving short-term, philanthropic business gestures towards NGOs) and a strategic frame (involving long-term, strategic relations between business and NGOs). It is proposed that businesses align with a strategic CSR frame (the business case) and as a consequence of resource dependence; NGOs align with an altruistic frame of CSR. A shift is, however, currently occurring as a convergence between business and NGO strategy becomes ever-more pronounced. A third collaborative CSR frame is thus evolving, resulting in a more commercial NGO approach and ensuing three strategic NGO options: fade (NGO fails to survive in the absence of sustainable funding sources); integrate with business (through mutually beneficial relationships) and transform (NGO becomes a self-sufficient, commercial entity). NGOs are gradually evolving from altruistic activities to constructive collaborations to strategic and sustainable self-sufficiency.